Childhood Obesity in America - Laura Dawes (Harvard University Press, 2014)
This book is about the changing environment of opinions, practices, and beliefs about childhood obesity in the twentieth century that surrounded and affected children like these— and many more like them. For Charley, at the beginning of the century, childhood obesity was a rare condition and one that doctors didn’t worry much about. Rather, a degree of plumpness in children was considered both attractive and beneficial. There was even some evidence that a degree of overweight in childhood protected children from infectious disease. Charley, his parents, and the Chicago Daily Tribune journalist who was interviewing them were proud that Americanborn Charley was fatter than another famous fat boy from Austria.